De-introducing the New Testament : texts, worlds, methods, stories - Penner, Todd C.; Ohio Library and Information Network (Chichester, West Sussex : Wiley Blackwell, 2015)
The critical focus in De-Introducing the New Testament on the modernist genre of writing and type of intellectual-cultural-political practice that is the "Introduction to the New Testament" is long overdue and much needed. The writers are bold and expansive in their critique and in their proposals. Their book merits serious attention. I hope it provokes sustained rethinking and reorientation. Vincent L. Wimbush, Institute for Signifying Scriptures
The order ofNew Testament things: questioning methods and meanings -- Foregrounding New Testament backgrounds: contextualizing interpretation -- Objects, objectives, and objectivities: material and visual culture and New Testament studies -- Brand(ish)ing biblical scholars(hip): New Testament studies and neoliberal subjectivity -- Back to the future: concluding observations on history, method, and theory in New Testament studies
Includes bibliographical references and index
Keywords: Bible. -- Criticism, interpretation, etc; Electronic books; Criticism, interpretation, etc